Alimentation quality determinants according to hospitalized patients - Mayumi Ikeda Morimoto, Ivone; Pacheco Paladini, Edson (O Mundo da Saúde, 2009)
This study aimed to determine the characteristics of the quality required for patients regarding alimentation during hospital internment. Patients interned in apartments and infirmaries of two general hospitals of Curitiba City-PR, answered a questionnaire that evaluated the relevance of nine characteristics of quality. Results showed that the characteristics of temperature, flavor, hygiene, menu, courtesy of feeding service and adequate utensils for meals were considered very important by hospitalized customers. The knowledge of hospital alimentation quality determinants must be the starting point for the development of strategies to care for necessities of customers, preventing that factors related to the service offered by the Unit of Feeding and Nutrition negatively influence the acceptance of foods by hospitalized patients.